Speak Up! Empowering Vocational EFL Students through Oral Corrective Feedback - Muhammad Andriana Gaffar; Raisya Azzahra Syaidina; Farida, Devi; Winulya, Farah Puji; Mufti , Dwiputri Marcella (Universitas Hamzanwadi, 2024)
Given the significance of corrective feedback in enhancing language learners’ speaking skills, especially in boosting accuracy and motivation, this study aims to examine the impact of direct oral corrective feedback (OCF) on Indonesian EFL learners. While research has shown that teacher feedback plays a crucial role in student performance, there is limited insight into how students interpret and engage with feedback—a factor essential to its effectiveness. Employing a descriptive qualitative research method, this study involved 39 vocational school students from SMK Medikacom in Bandung, Indonesia. Data were collected through classroom observations and semi-structured interviews, enabling a thorough exploration of students’ responses, behaviours, and attitudes toward Oral Corrective Feedback (OCF). Oral Corrective Feedback (OCF) improved students' speaking skills, with Recast, Clarification Request, and Repetition being the most common types and Recast being the most effective for error correction without disrupting communication. Students reported gains in pronunciation, grammar, fluency, confidence, and teacher-student rapport. Some students, however, felt discomfort with feedback, highlighting the need for a supportive, non-judgmental approach to prevent negative emotional impacts. This study suggests that while implicit feedback benefits advanced learners, lower-proficiency students may need more explicit correction. To maximise OCF’s impact, educators are encouraged to tailor feedback to individual proficiency levels and focus on fostering supportive, adaptive classroom environments.